The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1678-4162-9683
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação termográfica do desenvolvimento mamário de búfalas e sua regulação endócrina em distintos estágios fisiológicos

Abstract: RESUMO O conhecimento do desenvolvimento mamário de um rebanho leiteiro é fundamental, pois relaciona-se à eficiência produtiva. Objetivou-se avaliar a associação dos parâmetros térmicos mamários com concentrações hormonais de búfalas em distintos estágios fisiológicos. Foram utilizadas 24 búfalas mestiças Murrah, em quatro grupos (n= 6): grupo 1 (bezerras), grupo 2 (novilhas), grupo 3 (gestantes) e grupo 4 (lactantes). A cada 28 dias, durante 4 meses, realizaram-se exames de termografia digital por infraverme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…The surface temperature of the cranial and caudal cisterns was higher in the groups of calves and heifers (Chacur et al 2018), a finding that coincides with reports in the literature which mention that adult females have a higher proportion of adipose tissue in the mammary structure (Hovey and Aimo, 2010) that could act as a form of thermal insulation and, therefore, impede heat dissipation through the skin. Observations of the group of gestating buffaloes showed a correlation between rectal temperature and the temperature of the cranial-to-caudal teats that, in turn, was linked to the temperature of the cranial and caudal cisterns.…”
Section: Health Of the Udder Of Dairy Buffaloessupporting
confidence: 89%
See 2 more Smart Citations
“…The surface temperature of the cranial and caudal cisterns was higher in the groups of calves and heifers (Chacur et al 2018), a finding that coincides with reports in the literature which mention that adult females have a higher proportion of adipose tissue in the mammary structure (Hovey and Aimo, 2010) that could act as a form of thermal insulation and, therefore, impede heat dissipation through the skin. Observations of the group of gestating buffaloes showed a correlation between rectal temperature and the temperature of the cranial-to-caudal teats that, in turn, was linked to the temperature of the cranial and caudal cisterns.…”
Section: Health Of the Udder Of Dairy Buffaloessupporting
confidence: 89%
“…These results provide evidence of the existence of a connection between body temperature and the surface temperature of the udder that obeys the metabolic demands of both, and that can be studied using IRT (Chacur et al 2018), though it is necessary to keep in mind that temperatures can vary depending on the exact region of the udder evaluated, as shown in Figure 3. The thermograms in Figure 4 were taken immediately after automatic mechanical milking.…”
Section: Health Of the Udder Of Dairy Buffaloesmentioning
confidence: 80%
See 1 more Smart Citation
“…When studying the reproductive physiology of buffaloes, Chacur et al (2018), reported that inadequate management causes problems of embryo absorption and abortion in buffaloes, especially with respect to thermal stress. This problem can be early diagnosed, through a non-invasive technique such as infrared thermography.…”
Section: Gestation and Puerperiummentioning
confidence: 99%
“…The application of IRT in livestock production has been studied for several species such as beef cattle (Montanholi et al, 2009;LokeshBobu et al, 2018;Lowe et al, 2019;Vicentini et al, 2020), dairy cows (Chacur et al, 2016;Daltro et al, 2017;Schaefer et al, 2018;Sathiyabarathi et al, 2018;Tangorra et al, 2019;Deak et al, 2019), laying hen (Loyau et al, 2016), buffaloes (Barros et al, 2016;Sevegnani et al, 2016;Ahirwar et al, 2017;Ahirwar et al, 2018;Chacur et al, 2018), dairy sheep (Martins et al, 2013;Castro-Costa et al, 2014;Cannas et al, 2018;Byrne et al, 2019;Castells et al, 2019;Sutherland et al, 2020;Pulido-Rodríguez et al, 2021), dairy goats (Silva et al, 2014;Façanha et al, 2018), Broiler chickens (Nascimento et a., 2014;Candido et al, 2020), turkey (Moe et al, 2018) and pigs (Justino et al, 2014;Boileau et al, 2019), Table 2.…”
Section: Introductionmentioning
confidence: 99%